Occurrence and HAT-RAPD analysis of gastrointestinal helminths in domestic chickens (Gallus gallus domesticus) in Phayao province, northern Thailand - Preeyaporn Butboonchoo (2018)
© 2015 The present study determined the prevalence and distribution of gastrointestinal helminths in domestic chickens (Gallus gallus domesticus) between November 2012 and August 2013. One hundred and twenty domestic chickens were purchased from villages in four districts of Phayao province; Mae Chai, Dok Khamtai, Chun and Chiang Kham. Morphological differences were used to identify the helminth species, and HAT-RAPD technique was used to differentiate among closely related species. The results revealed that the total prevalence of infection was 99.2%. Cestode and nematode infections showed the highest prevalence in rainy season, while trematode infections were low and only found in hot season. The species and their prevalence were: Ascaridia galli (50.8%), Heterakis gallinarum (86.7%), Prosthogonimus macrorchis (1.7%), Echinostoma revolutum (0.8%), Raillietina echinobothrida (48.3%), Raillietina tetragona (57.5%), Raillietina cesticillus (12.5%), Raillietina sp. (35.8%), Cotugnia chiangmaii (14.2%) and Cotugnia sp. (32.5%). The prevalence of helminth infections did not differ significantly between male and female chickens. HAT-RAPD analysis, the specific fragment of 400 and 250 bp indicated that Raillietina sp. and Cotugnia sp. found, respectively, differ from other closely related species. This study has confirmed that HAT-RAPD technique can be used to differentiate among related species combined with morphological observations.